Robot-Assisted Oropharyngeal Reconstruction with Free Tissue Transfer - Bonawitz, Steven C.; Duvvuri, Umamaheswar (Journal of Reconstructive Microsurgery, 2012)
The surgical robot has been demonstrated to have useful applications in urologic, gynecologic, cardiac, general, and endocrine surgery. The development of robotic surgery has enhanced the precision and control of the surgeon in minimally invasive surgical situations specific to these specialties and, more recently, has been applied to the treatment of oropharyngeal tumors in the form of transoral robotic surgery (TORS). The elimination of the need for lip- and mandible-splitting approaches has allowed a reassessment of surgical options for the treatment of tumors that have until recently been primarily addressed nonoperatively with chemoradiation. The TORS approach has created the need to adapt current reconstructive options to robotic technology to manage the resultant tissue defects and to assess and compare the effectiveness of these procedures. This report details our early experience with the use of robot-assisted free tissue transfer for management of soft tissue defects of the oropharynx.
Keywords: robotic; TORS; free tissue transfer